﻿Repercussões sociais da violência contra crianças e adolescentes: deliqüência - Cela, Vânia Vaz Barbosa (2007)
This research is responsible for the investigation and problematization of the violence production process in children and teenagers through deviant behaviour, especially the drug s use and traffic, given that the deviant behaviour named juvenile criminality is something built and that can t be disassociated from the social and institutional relations that are ideological and violent, as well as the construction of, social and individual, positive identities can become important instruments for the process of democratization and the effective juvenile citizenship. In relation to the teorical referential, the work was developed from readings beyond the social science camp, without getting far from it, searching for support in other scientific camps and making your bases on Manuel Castells formulations about the power of the identity, and on Nancy Fraser and Axel Honneth in relation to the recognition struggle. In the empiric field, the discourses and graphic representations from twenty four children and teenagers that attend a social project were privileged, and compared to those shown at the documentary and the book Falcão Meninos do Tráfico produced by MV Bill, in relation to the social profile and life trajectory. From the study subjects' perspective, the data suggest that the children and the teenagers conceive violence as a natural thing, either as victims or persecutors. However, the research shows that, despite the subjects of the two studied groups reveled in your discourses the influence of the violent relations in their daily lives, the subjects got recognition during the process of identity construction by the groups with which they maintained the sense of belonging, either it being the family, the community or the school, they were positively influenced and established a positive representation of themselves and didn t show any deviant and violent tendency or behaviour. Therefore, we demonstrate the role of the school for an education for peace, as well as the participation of the family, the community and the stimulation of the juvenile protagonism as transforming practices, capable of awaking the citizenship and avoiding the construction of people that reproduce deviant and violent behaviour